Some new estimates of integral inequalities and their applications - Bayraktar, B.; Butt, S. I.; Nápoles, J. E.; Rabossi, F. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.9, 517.928 We obtain several new integral inequalities in terms of fractional integral operators for the functions whose first derivatives satisfy either the conditions of the Lagrange theorem or the Lipschitz condition. In some special cases, the results obtained provide better upper estimates than those known in the literature for Bullen-type inequality and Hadamard-type right-hand side inequality. Finally, some error estimates for the trapezoidal formula are discussed.